2022
DOI: 10.1039/d1np00022e
|View full text |Cite
|
Sign up to set email alerts
|

The chemical ecology of the fungus-farming termite symbiosis

Abstract: Since the early 1970s, 375 natural products have been identified from members of the fungus-farming termite symbiosis, and this review summarises and discusses the ecological implications of the presence of this vast chemical repertoire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 162 publications
(330 reference statements)
0
31
0
Order By: Relevance
“…[16] Based on our detailed analysis of the madurastatin-related GNPS network, three related compounds (2-4) were isolated and structurally identified based on 1D and 2D NMR analysis and HRMS/MS interpretation (Figure 3A). This deduction was verified by 2D NMR analysis ( 1 H-1 H COSY, HSQC, and HMBC correlations of H 2 -14/C-13, H 2 -14/C-16, and H 2 -15/C-16) and 3 J HH vicinal correlations between H 2 -14 and H 2 -15. To further proof the stereochemistry of compound 4, we also obtained two synthetic isomers of 4 a (D-serine) and 4 b (Lserine) and comparative 1D NMR analyses indicated identical chemical shift and J-coupling pattern between madurastatin G1 (4) and synthetic isomer salicyl-D-Ser-L-ala-ß-Ala-OH (4 a) (synthesized by Biosyntan GmbH), suggesting again the presence of D-serine in 4 (Figures S50-S61).…”
Section: Structural Elucidation Of Madurastatin Derivativesmentioning
confidence: 62%
See 1 more Smart Citation
“…[16] Based on our detailed analysis of the madurastatin-related GNPS network, three related compounds (2-4) were isolated and structurally identified based on 1D and 2D NMR analysis and HRMS/MS interpretation (Figure 3A). This deduction was verified by 2D NMR analysis ( 1 H-1 H COSY, HSQC, and HMBC correlations of H 2 -14/C-13, H 2 -14/C-16, and H 2 -15/C-16) and 3 J HH vicinal correlations between H 2 -14 and H 2 -15. To further proof the stereochemistry of compound 4, we also obtained two synthetic isomers of 4 a (D-serine) and 4 b (Lserine) and comparative 1D NMR analyses indicated identical chemical shift and J-coupling pattern between madurastatin G1 (4) and synthetic isomer salicyl-D-Ser-L-ala-ß-Ala-OH (4 a) (synthesized by Biosyntan GmbH), suggesting again the presence of D-serine in 4 (Figures S50-S61).…”
Section: Structural Elucidation Of Madurastatin Derivativesmentioning
confidence: 62%
“…Defensive symbiotic microorganisms of fungus farming insects have been shown to produce a diverse set of bioactive natural products to prevent detrimental infestations of the susceptible fungal monoculture. [1][2][3] We recently intensified our research efforts on elucidating the defensive functions of Actinobacteria in the fungus-farming termite Macrotermes natalensis [4,5] and found that most of the actinobacterial isolates produced mixtures of secondary metabolites that are active against the co-occurring weed fungi. Within these studies, we became particular intrigued by members of the fairly underexplored genus Actinomadura, [6][7][8] including Actinomadura sp.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetically, it is close to two viruses, Agaricus bisporus virus 9 and Lentinula edodes deltaflexivirus 2, both found in edible basidiomycete mushrooms [ 31 , 32 ]. This is noteworthy, considering that M. carbonarius (where deltaflexi-like contigs were detected) is a species that cultivates basidiomycete fungi of the genus Termitomyces (Agaricales) as a food source [ 33 ]. If these deltaflexi-like contigs indeed form parts of a viral genome, then the virus is not likely to infect termites, but fungi cultivated by termites.…”
Section: Discussionmentioning
confidence: 99%
“…The highest diversity of insects in the world is found in Brazil (Rafael et al 2009), so ecological-based research of specialized metabolites mediating insect-microbial symbiosis would represent a new and underexplored approach in the field of Natural Products Chemistry in the country. Previous remarkable results have described specialized metabolites mediating microbial symbiosis in termites, beetles, wasps and Attine ants (Van Arnam et al 2018, Schmidt et al 2022, Kroiss et al 2010), all collected outside Brazil. These data were the basis for the establishment of the first International Cooperative Biodiversity Group (ICBG) in Brazil, bringing together a team of researchers from the US (Harvard Medical School, University of Wisconsin-Madison) and Brazil (University of São Paulo).…”
Section: Microorganisms Associated To Insectsmentioning
confidence: 99%